Optimalisasi Pengendalian Persediaan Tepung Terigu di UMKM Agung Bakery - Aristawidya, Raihana; Usman , Yulita Veranda (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2025)
Agung Bakery, a small and medium-sized enterprise (UMKM), produces various types of bread, with pizza bread being one of its flagship products. The demand for pizza bread often fluctuates, posing challenges in optimally managing the inventory of wheat flour raw materials. This study aims to control raw material inventory using the Material Requirement Planning (MRP) method to reduce costs and improve efficiency. The demand forecast for pizza bread for the next year was analyzed using the Linear Regression method. Based on the forecast, the annual requirement for wheat flour raw materials is 4,713 kg. The MRP method with the Lot for Lot (LFL) technique was applied to determine the optimal order quantity and inventory costs. The analysis results show that the order quantity for wheat flour raw materials from March 2024 to February 2025 is 4,700 kg or 188 sacks. The total annual inventory cost is IDR 38,178,717, resulting in a cost efficiency of approximately 4.88%. The application of MRP with the LFL technique also effectively reduced the Bullwhip Effect from 1.85 to 0.12, indicating better control over demand variability.